Analysis and diagnosis of timber structures in Porto historical centre - T. Ilharco (2008)
The historical centre of Porto was considered in 1996 UNESCO World Heritage to the outstanding universal value of the site, with urban fabric and historic buildings that bear remarkable testimony to the development over the past thousand years of an important European city". In order to contribute to the maintenance of this remarkable set of buildings, with historical, architectural, constructive and heritage value, in opposition to the continuous build heritage degradation process and the population dislocation from the centre to the surroundings, NCREP-FEUP have been participating in many rehabilitation projects, analyzing the conservation state of building structural elements (stone masonry walls and timber floors and roofs). The focus of the present paper is given to the evaluation of the physical state of timber structural elements, namely to the various instruments used on the Analysis and Diagnosis phases, in particular to the non destructive (NDT), medium-destructive (MDT) and, in a certain context, destructive testing techniques.